The first quiescent galaxies in TNG300. Issue 2 (19th April 2023) - Hartley, Abigail I; Nelson, Erica J; Suess, Katherine A; Garcia, Alex M; Park, Minjung; Hernquist, Lars; Bezanson, Rachel; Nevin, Rebecca; Pillepich, Annalisa; Schechter, Aimee L; Terrazas, Bryan A; Torrey, Paul; et al.
ABSTRACT: We identify the first quiescent galaxies in TNG300, the largest volume of the IllustrisTNG cosmological simulation suite, and explore their quenching processes and time evolution to z = 0. We find that the first quiescent galaxies with stellar masses M * > 3 × 10 10 M⊙ and specific star formation rates sSFR < 10 −11 yr −1 emerge at z ∼ 4.2 in TNG300. Suppression of star formation in these galaxies begins with a thermal mode of active galactic nucleus feedback at z ∼ 6, and a kinetic feedback mode acts in each galaxy by z ∼ 4.7 to complete the quenching process, which occurs on a time-scale of ∼0.35 Gyr. Surprisingly, we find that the majority of these galaxies are not the main progenitors of their z = 0 descendants; instead, four of the five galaxies fall into more massive galaxies in subsequent mergers at a range of redshifts 2.5 < z < 0.2. By z = 0, these descendants are the centres of galaxy clusters with average stellar masses of 8 × 10 11 M⊙ . We make predictions for the first quenched galaxies to be located by the JWST .